(untitled) (Journal of Global Humanities and Social Sciences, 2024)
In recent years, the rapid development and expanding application scope of UAV technology have made it an important force in promoting the development of the Low-Altitude Economy. A Low-Altitude Economy involves many fields such as Low-Altitude tourism, short-haul transportation, navigation logistics, emergency rescue, flight training, and Low-Altitude advertising, covering a wide range from infrastructure construction to high-end services. With its high flexibility, high efficiency, and wide range of application scenarios, UAVs are gradually showing great potential and value in these fields. The purpose of this paper is to discuss the current situation, application, and strategy of the synergistic development of the drone industry and Low-Altitude Economy, to provide a scientific theoretical basis and practical guidance, and to promote the deep integration and common development of the two.